New method of high-energy gamma ray direction reconstruction in multilayered converters. (November 2019) - Kheymits, M D; Galper, A M; Arkhangelskaya, I V; Arkhangelskiy, A I; Bakaldin, A V; Gusakov, Yu V; Dalkarov, O D; Djivelikyan, E A; Egorov, A E; Leonov, A A; Naumov, P Yu; Pappe, N Yu; et al.
Abstract: A new method of high-energy gamma ray incident direction reconstruction is developed for gamma-ray detectors with multilayered converters. The method uses data from converter and, if available, from position-sensitive calorimeter to reconstruct an electromagnetic cascade axis and to determine the incident direction of a primary gamma. For the first time to find point of intersection of gamma direction line with convertor plane, median of energy deposit in sensitive plane of convertor is used. Applied, for example, to the GAMMA-400 space-based gamma-ray telescope this method allowed to achieve the angular resolution ∼0.01° at gamma-ray energy of 100 GeV, being much better than accuracy of the past and present space- and ground-based experiments. In the algorithm presented, a balance between the angular resolution and the effective area can be found to meet a scientific goal of an experiment.